Scientific Computing: For Scientists and Engineers - Heister, Timo; Rebholz, Leo G (De Gruyter Textbook, 2015)
Scientific Computing for Scientists and Engineers is designed to teach undergraduate students relevant numerical methods and required fundamentals in scientific computing.Most problems in science and engineering require the solution of mathematical problems, most of which can only be done on a computer.